Soft X-ray core-level spectroscopy studies of molecules on TiO2 surfaces in the context of light harvesting - Ahmed, M H Mesbah (2023)
Studying the interaction between the dye and the surface as well as how the system reacts to light is important for understanding the electrical and chemical characteristics of dye sensitised solar cells (DSSC). In this thesis, several model systems relevant to dye sensitised solar cells have been investigated for further understanding. But, this thesis starts with the investigation on the popular semiconductor for DSSC application, rutile TiO2(110). At first, the annealing induced migration of defects in single crystals of rutile titanium dioxide have been investigated, and then the next chapter, investigates how defects interact with the molecules of oxygen, water, and air.